The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/sms.14147
|View full text |Cite
|
Sign up to set email alerts
|

Comparing estimates of physical activity in children across different cut‐points and the associations with weight status

Abstract: This study aimed to compare sedentary time (SED) and intensity-specific physical activity (PA) estimates and the associations of SED and PA with body mass index (BMI) and waist circumference (WC) using three different sets of cut-points in preschool-aged children. A total of 751 children (4.7 ± 0.9 years, boys 52.7%) wore an ActiGraph GT3X+BT accelerometer on their hip for 7 days (24 h). Euclidean norm −1 G with negative values rounded to zero (ENMO) and activity counts from vertical axis (VACounts) and vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
(175 reference statements)
1
8
0
1
Order By: Relevance
“…A detailed description of study characteristics can be seen in Supplementary Material 2 . Overall, seven studies were conducted exclusively in the United States [ 37 44 ], five in Canada [ 34 , 45 – 48 ], five in Australia [ 49 53 ], four in China [ 54 – 57 ], three in Belgium [ 58 60 ], three in South Africa [ 61 – 63 ], three in Brazil [ 64 66 ], two in the United Kingdom [ 67 , 68 ], two in Sweden [ 69 , 70 ], two in Japan [ 71 , 72 ], two in Poland [ 73 , 74 ], and a single study each from Switzerland [ 75 ], Bangladesh [ 76 ], Denmark [ 77 ], Finland [ 19 ], Norway [ 78 ], Portugal [ 79 – 82 ], Singapore [ 83 ], and Vietnam [ 84 ]. Additionally, there was one international study that included children from multiple European countries [ 85 ], and one intercontinental study which included children from Europe and United States [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of study characteristics can be seen in Supplementary Material 2 . Overall, seven studies were conducted exclusively in the United States [ 37 44 ], five in Canada [ 34 , 45 – 48 ], five in Australia [ 49 53 ], four in China [ 54 – 57 ], three in Belgium [ 58 60 ], three in South Africa [ 61 – 63 ], three in Brazil [ 64 66 ], two in the United Kingdom [ 67 , 68 ], two in Sweden [ 69 , 70 ], two in Japan [ 71 , 72 ], two in Poland [ 73 , 74 ], and a single study each from Switzerland [ 75 ], Bangladesh [ 76 ], Denmark [ 77 ], Finland [ 19 ], Norway [ 78 ], Portugal [ 79 – 82 ], Singapore [ 83 ], and Vietnam [ 84 ]. Additionally, there was one international study that included children from multiple European countries [ 85 ], and one intercontinental study which included children from Europe and United States [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among studies not included in the meta-analysis, one reported that 80-90% of children achieve the overall physical activity recommendation [ 72 ], two reported that between 70 and 80% achieve the recommendation [ 19 , 67 ], one reported that between 60 and 70% of children achieved the recommendation [ 46 ], one reported that between 50 and 60% achieved the recommendation, [ 47 ], one reported that between 10 and 20% of children achieved the recommendation [ 45 ], and one reported that between 0 and 10% of children achieved the recommendation [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe this to be a positive finding, considering the many health benefits that result from maintaining high levels of PA ( Poitras et al, 2016 ; Chaput et al, 2020 ). However, we also recognize that high levels of PA in research with children and adolescents are often attributable to methodological decisions ( Kim et al, 2017 ; Llorente-Cantarero et al, 2021 ; Leppänen et al, 2022 ). We have used standardized protocols and recommended acceleration cut-off points for the age-group of our sample ( Migueles et al, 2017 , 2019 ), and thereby, our results are comparable to several studies that used the same methods.…”
Section: Discussionmentioning
confidence: 99%